Mutual Impedance Probe in Collisionless Unmagnetized Plasmas With Suprathermal Electrons—Application to BepiColombo - Gilet, Nicolas; Henri, Pierre; Wattieaux, Gaëtan; Myllys, Minna; Randriamboarison, Orélien; Béghin, Christian; Rauch, Jean-Louis (Frontiers in Astronomy and Space Sciences, 2019)
Context: Mutual impedance experiments are active electric probes providing in-situ space plasma measurements. Such active experiments consist of a set of electric antennas used as transmitter(s) and receivers(s) through which various dielectric properties of the plasma can be probed, giving therefore access to key plasma parameters such as, for instance, the electron density or the electron temperature. Since the beginning of the space exploration, such active probes have been launched and operated in Earth's ionospheric and magnetospheric plasmas. More recently and in the coming years, mutual impedance probes have been and will be operated onboard exploratory planetary missions, such as Rosetta, BepiColombo and JUICE, to probe the cometary plasma of 67P/Churyumov-Gerasimenko, the Hermean and the Jovian magnetospheres, respectively. Aims: Some analytic modeling is necessary to calibrate and analyse mutual impedance observations in order to access to macroscopic bulk plasma quantities. In situ particle observations from various space missions have confirmed that space plasmas are out of local thermodynamic equilibrium. This means that particle velocity distributions can be far from a Maxwellian distribution, exhibiting for instance temperature anisotropies, beams or a suprathermal population. The goal of this paper is to characterize the effect of suprathermal electrons on the instrumental response in order to assess the robustness of plasma diagnostics based on mutual impedance measurements in plasmas characterized by a significant amount of suprathermal particles. Methods: The instrumental response directly depends on the electron velocity distribution function (evdf). In this work, we choose to model suprathermal electrons by considering different approaches using: (i) a kappa evdf, (ii) a double-Maxwellian evdf or (iii) a mix of a Maxwellian evdf and a kappa evdf. For each case, we compute the spatial distribution of the electrostatic potential induced by the transmitters, discretized and modeled here as an ensemble of pulsating point charges. Results: We apply our modeling by building synthetic mutual impedance spectra of the PWI/AM2P probe, lauched in October 2018 onboard the Mercury Magnetospheric Orbiter (MIO/MMO) spacecraft of the BepiColombo exploratory space mission, in order to calibrate and analyse the future electron observations in the plasma environment of Mercury.